Aplikasi Audio Al-Qur’an Untuk Membantu Mengingat Hafalan Al-Qur’an Menggunakan Framework Django - Innas Shofa Uzzahro; Dwi Sakethi; Didik Kurniawan; Machudor Yusman (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
The Quran serves as a fundamental guide and legal foundation for the lives of Muslims. As practicing Muslims, it is essential to read, listen to, and commit it to memory. To aid in the memorization process, one can utilize Quranic audio as a learning tool to enhance pronunciation and recitation skills through repeated listening and reciting. In this study, an application for Quranic audio was developed using the Django Framework. The aim of this application is to assist Quran memorizers in their memorization journey by providing easy access to audio verses of the Quran. The research employed the waterfall methodology, involving stages such as needs analysis, application design, code development, testing, and application maintenance. The Audio Quran application offers 30 Juz' of Quranic audio verses with a selection of sheikhs. After testing with students and general users, the application achieved an impressive average user satisfaction score of 88.00%.